2020
DOI: 10.1016/j.jcyt.2020.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Pancreas-derived mesenchymal stromal cells share immune response-modulating and angiogenic potential with bone marrow mesenchymal stromal cells and can be grown to therapeutic scale under Good Manufacturing Practice conditions

Abstract: Background aims: Mesenchymal stromal cells (MSCs) isolated from various tissues are under investigation as cellular therapeutics in a wide range of diseases. It is appreciated that the basic biological functions of MSCs vary depending on tissue source. However, in-depth comparative analyses between MSCs isolated from different tissue sources under Good Manufacturing Practice (GMP) conditions are lacking. Human clinical-grade low-purity islet (LPI) fractions are generated as a byproduct of islet isolation for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
(38 reference statements)
1
7
0
Order By: Relevance
“…On the other hand, the colony-forming efficiency of Gal KO apBM-MSCs in this report is 18.3%. This value was close to the colony-forming efficiency of human bone marrow-and pancreas-derived MSCs (about 10%) reported by Thirlwell et al 10 and the colony-forming efficiency of human adipose tissue-derived MSCs (about 20%) reported by Fujita et al 11 Gal antigen is negative in human, 12 therefore, Gal antigen may have some role in the process of cell adhesion and colony formation. Considering proliferation rates are similar between the WT apBM-MSCs and Gal KO apBM-MSCs (Figure 3), we speculate that low colony-forming ability is associated with low expression of adhesion molecule in Gal KO apBM-MSCs.…”
Section: Discussionsupporting
confidence: 88%
“…On the other hand, the colony-forming efficiency of Gal KO apBM-MSCs in this report is 18.3%. This value was close to the colony-forming efficiency of human bone marrow-and pancreas-derived MSCs (about 10%) reported by Thirlwell et al 10 and the colony-forming efficiency of human adipose tissue-derived MSCs (about 20%) reported by Fujita et al 11 Gal antigen is negative in human, 12 therefore, Gal antigen may have some role in the process of cell adhesion and colony formation. Considering proliferation rates are similar between the WT apBM-MSCs and Gal KO apBM-MSCs (Figure 3), we speculate that low colony-forming ability is associated with low expression of adhesion molecule in Gal KO apBM-MSCs.…”
Section: Discussionsupporting
confidence: 88%
“…CXCL8 (also known as IL-8) secretion is one of the significant characteristics of MSCs. 51 , 52 Although we could not investigate the relative secretion of CXCL8 to other chemokines, single plex analysis confirmed that bone marrow-derived MSCs secrete CXCL8 which are further upregulated by IFNγ and TNFα ( Supplementary Fig. S5 ).…”
Section: Discussionmentioning
confidence: 94%
“…The pattern of chemokines and pro-regenerative factors in islet-derived MSCs is similar to that of BM-MSCs, and they have been shown to have immunomodulatory properties such as that of suppressing T cell proliferation in vitro. 37 Islet-derived MSCs do not express insulin; however, compared to BM-MSCs, their level of histone modification of the insulin gene is closer to that of islets. 46 Furthermore, some reports have suggested that MSCs established from pancreatic tissue may contribute to islet regeneration by producing more secreted substances involved in vascular development, wound healing, and chemotaxis than BM-MSCs.…”
Section: Discussionmentioning
confidence: 95%
“…Clinical-grade npISLET-MSCs also need to be investigated using GMP-compliant materials in the future, as is being done for the GMP manufacturing of human islet MSCs. 37 It is also known that various factors in the production of MSCs, such as source tissue, isolation protocols, media composition, and pre-treatment, affect the chemokine expression, immunomodulatory capacity, and therapeutic efficacy of MSCs. 38 For npISLET-MSCs, there is insufficient information about secreted products, chemokines, and other characteristics that affect their therapeutic effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation